Fundamental values of administration of justice: An appraisal of the dispensation of justice in Bangladesh - Islam, Mohammad Saiful (IIUC Studies, 2026)
Administering justice is a critical role of the state that recognizes individuals' rights, assures impartial reprisal for wrongdoing, and promotes communal harmony. The judicial institution serves as the central mechanism for the proper administration of justice. To reach the right judgment, a fair, independent, and unbiased judicial process is essential. The legal system has thrived as a result of certain essential values that uphold the highest level of fairness and impartiality. As a result, Bangladesh's administration of the justice system cannot fall far behind. Since the judicial institution is at the center of the administration of justice, the research initially focuses on a thorough examination of the widely acknowledged essential core values in the judicial system. Second, the article seeks to assess Bangladesh's justice system's conformity to the justice system's inclusive essential values. Finally, the research concludes that Bangladesh's justice system has secured practically all essential principles through constitutional and legislative endorsement. Nonetheless, due to several shortcomings, the efficient legal process and accessibility of the justice system have been questioned. IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 67-90